MARKET REACTIONS TO THE CORPORATE INCOME TAX RATE REDUCTION - Khodijah, Amalia Siti; Ardhiyansah, Ardhiyansah; Muqorrobin Hujjah , Al Jaber; Anisa Wara Rahmayanti, Anggraeni (LP2M Universitas Perjuangan Tasikmalaya, 2023)
This research aims to investigates market reactions to the announcement of the corporate income tax rate reduction regulated by the government of Indonesia. An event study employed to observe of the market reaction to the Press Release provided by the Indonesian Directorate General of Taxes regarding the Implementation of the Corporate Income Tax Rate Reduction in Income Taxes Article 29 Calculation and Income Taxes Article 25 Installment. A Dimson’s model and a z-test are employed to investigate whether market reactions exist around the new tax rate announcement. The sample used in the research is all non-financial companies listed in the Indonesia Stock Exchange (IDX). This research finds that the market reaction found significantly to the corporate income tax reduction announcement by calculating in a short window observation. This research contributes to the literature, investors and regulator for investment decision and evaluating the policy.